Pirasat dan Kitab Taj As Salatin: Tinjauan Poskolonialisme pada Ilmu Fisiognomi - Haekal Rheza Afandi; Turita Indah Setyani (Jumantara: Jurnal Manuskrip Nusantara, 2023)
Traces of the past can be seen in Pirasat and Taj As Salatin which show the attitude of locals towards foreign nations. This study aims to reveal the resistance of the locals as reflected in the two texts to add information about the history of the colonial period in Indonesia. This study will use a literature comparison method with a postcolonial review as the main instrument in reviewing the resistance of locals to the invaders in the Pirasat and Taj As Salatin. The form of resistance is shown by the locals by giving bad descriptions of people with the physical shape or form of the invaders, like blue eyes (embarrassing) and yellow hair (not virtuous). The mention of these body parts refers to Europeans as evidenced by the presentation of the distribution of blue eyes and yellow hair which are very common in that region. The results of the research from the two texts show that the locals have shown passive-aggressive resistance as seen from the physical mention of the invaders who although not explicitly stated as colonizers, it is certain that there can be no locals with that physical description.